My life is weapon: a modern history of suicide bombing - Reuter, Christoph; Ragg-kirkby, Helena. (Tr.) (New Delhi, 2005)
What kind of people are suicide bombers? How do they justify their actions? In this meticulously researched and sensitively written book, journalist Christoph Reuter argues that popular views of these young men and women - as crazed fanatics or brainwashed automatons - fall short of the mark. In many cases these modern-day martyrs are well-educated young adults who turn themselves into human bombs willingly and eagerly - to exact revenge on a more powerful enemy, perceived as both unjust and oppressive. Suicide assassins are determined to make a difference, for once in their lives, no matter what the cost. As Reuter's many interviews with would-be martyrs, their trainers, friends, and relatives reveal, the bombers are motivated more by how they expect to be remembered - as heroic figures - than by religion-infused visions of a blissful life to come. Reuter, who spent eight years researching the book, moves from the broken survivors of the childrens' suicide brigades in the Iran-Iraq war of the 1980s, to the war-torn Lebanon of Hezbollah, to Israeli-occupied Palestinian land, and to regions as disparate as Sri Lanka, Chechnya, and Kurdistan. He tells a disturbing story of the modern globalization of suicide bombing - orchestrated, as his own investigations have helped to establish, by the shadowy Al Qaeda network and unintentionally enabled by wrong-headed policies of Western governments. In a final, hopeful chapter, Reuter points to today's postrevolutionary, post-Khomeini Iran, where a new social environment renounces the horrific practice in the very place where it was enthusiastically embraced just decades ago.
Keywords: Terrorism